Arthroscopic-Assisted TFCC Foveal Tear Reattachment with Around Styloid Technique - Mantovani, Gustavo; Estrada, Camilo; Auto, Sergio; Azocar, Camila; Villegas, Robin; Lenzi, Luiz (Journal of Wrist Surgery, 2025)
Traumatic or degenerative changes in the triangular fibrocartilage complex (TFCC) commonly cause ulnar-sided wrist pain and dysfunction. Arthroscopic techniques for the treatment of these injuries have gained popularity due to their minimally invasive nature and improved visualization.This article presents a novel arthroscopic technique for TFCC repair named Around Styloid. This is a modification of an open technique described by Argintar and Mantovani in 2010. This technique seeks to simplify the technique of foveal reinsertion of the TFCC, using basic elements and sutures in surgery.Traditional open techniques for TFCC repair can be technically demanding and may involve bony tunneling in the foveal joint region of the distal ulna. Arthroscopic techniques have emerged as a less invasive alternative, but they can still present challenges, particularly for surgeons with limited experience.The arthroscopic “Around Styloid” novel technique appears as an alternative that seeks, in a simple way, to perform foveal reinsertion of the TFCC, avoiding the need to perform the bone tunnels directed to the fovea of the ulna, which may represent a great surgical challenge, especially for surgeons in the process of learning arthroscopic techniques.
Keywords: arthroscopy; TFCC; instability; foveal; repair